Analisis Kebutuhan Peserta Didik terhadap Lembar Kerja Peserta Didik Terintegrasi Science, Technology, Engineering, Arts, And Mathematics Tentang Materi Sistem Peredaran Darah untuk Peserta Didik Fase F - Zulyusri Zulyusri; Astri Humaira (GURUKU : Jurnal Pendidikan dan Sosial Humaniora, 2025)
This study aims to analyze the needs of students for the development of Student Worksheets (LKPD) integrated with the STEAM (Science, Technology, Engineering, Arts, and Mathematics) approach on circulatory system materials for Phase F students. Data was obtained through interviews with biology teachers and the distribution of questionnaires to 33 students in grade XI of SMA Negeri 3 Pariaman. The results of the study show that the LKPD that has been used has not adopted the STEAM approach, tends to be monotonous, and has not been able to optimally meet the learning styles and needs of students. Students show a high interest in Biology and want learning media that is interactive, visual, and uses language that is easy to understand. As many as 100% of respondents expressed interest in STEAM-based LKPD, especially for circulatory system materials that are considered difficult and complex. Thus, the results of this analysis become an important basis for the development of relevant and innovative LKPDs to support fun and meaningful 21st century learning.